2006
DOI: 10.1080/02772240600727428
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary-butyl acetate metabolism, toxicity, and human health considerations

Abstract: Tertiary-butyl acetate (TBAC) is an organic solvent with a potential for occupational and environmental exposure as a result of its use in industrial coatings, adhesives, inks, and degreasers. The objective of these studies was to extend the toxicological database upon which health hazard and risk assessments of TBAC can be made. The metabolism of TBAC was studied in rats exposed by inhalation for 6 h to concentrations of 100 or 1000 ppm. There was an evidence of partial saturation of TBAC absorption and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…As the radioactivity detected in the tissues after exposure to a concentration ten times higher was less than ten times higher, the authors concluded that there might have been a partial saturation of absorption and metabolism at the higher concentrations (Cruzan and Kirkpatrick 2006).…”
Section: Absorption Distribution and Eliminationmentioning
confidence: 99%
See 2 more Smart Citations
“…As the radioactivity detected in the tissues after exposure to a concentration ten times higher was less than ten times higher, the authors concluded that there might have been a partial saturation of absorption and metabolism at the higher concentrations (Cruzan and Kirkpatrick 2006).…”
Section: Absorption Distribution and Eliminationmentioning
confidence: 99%
“…Based on the proportion of metabolites that are formed, tert-butyl acetate is primarily hydroxylated at 100 ml/m 3 (altogether 24% of all metabolites), while ester hydrolysis prevails at 1000 ml/m 3 (altogether 23% of all metabolites), 70% to 80% of the ester being cleaved. Oxidation of the acetate unit (1.3% at 100 ml/m 3 ; 0.6% at 1000 ml/m 3 ) is a third metabolic pathway, but it is of minor relevance; glucuronidation is another minor route (Figure 1; Cruzan and Kirkpatrick 2006).…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxylation of the tert-butyl side chain appears to predominate at lower exposures whilst hydrolysis predominates at higher exposures. Oxidation of the acetate side chain can also occur to a minor extent (Cruzan and Kirkpatrick, 2006). tert-Butanol is not a substrate for alcohol dehydrogenase and is metabolised only slowly, either by glucuronide conjugation of the hydroxyl group, with excretion in the urine, or oxidation of one or more of the alkyl substituents, which can be catalysed by P450 enzymes.…”
Section: Previous Evaluationsmentioning
confidence: 99%
“…In the absence of any human counterpart to this protein at levels sufficient to support a toxicologically relevant interaction, this carcinogenic response is considered not relevant to humans (Cruzan and Kirkpatrick, 2006;TERA, 2009). The follicular cell adenomas in female mice were accompanied by follicular cell hyperplasia.…”
mentioning
confidence: 99%